Microstructural understanding of the oxidation and inter-diffusion behavior of Cr-coated Alloy 800H in supercritical water. (February 2023) - Yang, Jianqiao; Bai, Shuyuan; Sun, Jiyuan; Wu, Hao; Sun, Shenghan; Wang, Shuzhong; Li, Yanhui; Ma, Wenhao; Tang, Xingying; Xu, Donghai
Abstract: In this study, corrosion tests were performed on Cr-coated Alloy 800 H in 500 °C supercritical water, containing 6000 mg∙L −1 oxygen, for 500 h. After exposure, the structure of the sample can be divided into a Cr2 O3 layer with a nanocrystal structure, a residual Cr coating with columnar or equiaxed Cr grains, an inter-diffusion layer including Fe-Ni-rich and Cr-O-rich zones, and an alloy substrate. Transmission electron microscopy was employed for the high-resolution analysis of atom diffusion in the sample. The outward diffusion of Fe and Ni was restrained by the coating, and no oxide exfoliation was observed. Highlights: A 15 µm Cr coating was prepared on a Alloy 800 H alloy. Cr2 O3 nanocrystal structure formed on the sample surface. Outward diffusion of Fe and Ni was restrained by the coating. Grain boundary diffusion of Fe observed by TEM.